Effects of simulated digestion and prebiotics properties of polysaccharides extracted from Imperatae Rhizoma based on different pilot processes - Sun, Mengge; Huang, Haotian; Tang, Haibao; Chen, Jiajie; Chen, Wei; Yang, Dongsheng (Frontiers in Microbiology, 2025)
Recent studies have highlighted the prebiotic potential of natural plant polysaccharides, demonstrating their role in promoting beneficial gut microbiota and improving health. However, research on the digestive properties and prebiotic activities of Imperatae Rhizoma Polysaccharides (IRPs) remains limited. This study investigated fresh Imperatae Rhizoma as the research object. After processing, dry Imperatae Rhizoma and carbonized Imperatae Rhizoma were prepared. Three polysaccharides from the fresh, dry, and carbonized Imperatae Rhizoma were extracted with traditional hot water. And another polysaccharide was obtained by cold water extraction from fresh Imperatae Rhizoma. Total four IRPs were extracted and named: IRPs-F, IRPs-D, IRPs-C, and IRPs-J. This study evaluated the prebiotic activity of four polysaccharides derived from the roots of thatch, demonstrating their resistance to digestion, their ability to promote probiotic growth, and their enhancement of short-chain fatty acid (SCFA) production. The final results show that four IRPs exhibit strong resistance to digestion and IRPs-F ability to promote the growth of beneficial probiotics, making it a promising candidate for functional foods aimed at improving intestinal health, immune regulation, and metabolic benefits. This research is highly relevant to food microbiology and holds significant potential for application in the functional food and gut health sectors.